IMPLEMENTASI FUNGSI MANAJEMEN DALAM PELAKSANAAN PROGRAM PEMERINTAH DESA OMBOLATA KECAMATAN GUNUNGSITOLI IDANOI - Lifeit Darmil Gea; Eliagus Telaumbanua; Odaligoziduhu Halawa; Robin Markus Putra Waruwu (Jurnal Publikasi Manajemen Informatika, 2026)
This study aims to analyze the implementation of management functions in the execution of government programs in Ombolata Idanoi Village, Gunungsitoli Idanoi District. The research focuses on four key management functions: planning, organizing, actuating, and controlling, as well as the supporting and inhibiting factors in their implementation. A qualitative approach was employed, using interviews, observations, and documentation with the village head, village officials, and community members as data sources. The findings reveal that program planning was conducted through village meetings, yet community participation remained low. Organizing was carried out based on the established structure, but limited human resources and budget constraints posed major challenges. The implementation of physical programs, such as road and health facility development, was successful due to strong community cooperation. However, non-physical programs such as economic empowerment were less effective. Control functions were mostly administrative and lacked active community involvement. The main supporting factors included village funds, community solidarity, and technical support from the city government, while inhibiting factors involved budget limitations, inadequate human resources, low community participation, and weak socialization. This study highlights the importance of optimizing management functions to enhance the effectiveness of village government programs.